2020
DOI: 10.3390/transplantology1020012
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Dimensions in Hemodialysis Patients on Kidney Transplant Waiting List: Preliminary Data

Abstract: Although the donation rate for deceased and living kidneys has been increasing, the donor organ availability meets only the 30% of kidney needs in Italy. Consequently, hemodialysis patients stay for a long time, an average of 3.2 years, on a waiting list for a kidney transplant with consequent relevant psychological distress or even full-fledged psychiatric disorders, as diagnosed with traditional psychiatric nosological systems. Recent studies report, however, a higher prevalence of other psychosocial syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…These findings are consistent with those of other studies, which frequently reported on the association between psychological disturbances and various other physical diseases among patients [10,34,51]. Therefore, the tendencies shown in this study are understandable, as patients with ESRD are often worried about the unknown factors of their condition, based on a fear that they may lose their renal functions and experience other unexpected outcomes [10,34,50,51].…”
Section: Impact Of Mental State On Choosing Between Pekt and Pdktsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with those of other studies, which frequently reported on the association between psychological disturbances and various other physical diseases among patients [10,34,51]. Therefore, the tendencies shown in this study are understandable, as patients with ESRD are often worried about the unknown factors of their condition, based on a fear that they may lose their renal functions and experience other unexpected outcomes [10,34,50,51].…”
Section: Impact Of Mental State On Choosing Between Pekt and Pdktsupporting
confidence: 92%
“…It is well-known that anxiety plays important roles in the psychological and biological risk factors for the impairment of emotional perception/cognition [50]. The trait anxiety of the recipients enhanced negative mental responses (POMS-TA/POMS-D and POMS-C) in the selection between PDKT, and PEKT, respectively.…”
Section: Impact Of Mental State On Choosing Between Pekt and Pdktmentioning
confidence: 98%
See 2 more Smart Citations
“…Awareness of the presence of subclinical depressive disorders among both dialysis patients and their physicians is of great importance. A recently published study [ 46 ] showed a high percentage of hemodialysis patients affected by undetected syndromes such as irritability identified by the Diagnostic Criteria for Psychosomatic Research (DCPR) [ 47 ]. This report is congruent with data from a pilot study, which found that the prevalence of depression among hemodialysis patients was 30%.…”
Section: Discussionmentioning
confidence: 99%